New Current-Mode Oscillators Using a Single Unity-Gain Current-Follower - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A general circuit for realizing current-mode oscillators using a single negative unity-gain current-follower is presented. Using this circuit new oscillators of this class can be discovered systematically. Simulation results obtained from three new circuits are presented. The feasibility of obtaining a quadrature oscillator is investigated.